EVALUASI INKLUSIVITAS TATA PAMER INTERAKTIF DAN MULTISENSORI MUSEUM BERBASIS INTEGRATED MUSEUM ENGAGEMENT MODEL (IMEM): EVALUASI INKLUSIVITAS TATA PAMER INTERAKTIF DAN MULTISENSORI MUSEUM BERBASIS INTEGRATED MUSEUM ENGAGEMENT MODEL (IMEM) - Parlindungan Ravelino; Andryanto Rikrik Kusmara; Gregorius Prasetyo Adhitama (Universitas Telkom, 2026)
Abstract : Limited visitation and public engagement remain major issues for museums in Indonesia, indicating that the transition toward the New Museology paradigm has not yet been fully accompanied by inclusive exhibition practices. One emerging effort is the implementation of interactive and multisensory exhibition design; however, its effectiveness in supporting museum inclusivity still requires critical evaluation. This study aims to evaluate the inclusivity of interactive and multisensory exhibition design in Indonesian museums based on the Integrated Museum Engagement Model (IMEM), with the Bank Indonesia Museum and the Wayang Museum in Jakarta as case studies. This research employed a mixed-methods approach through field observation, visual documentation, and questionnaires distributed to museum visitors. The analysis used the three pillars of IMEM, namely Participatory Design, Narrative Immersion, and Digital Interaction, as an evaluative framework. The findings show that both museums have adopted various interactive elements, such as touchscreens, immersive spaces, audio-visual media, and digital modelling, which contribute to increased visitor engagement. However, these implementations have not fully supported inclusivity. Limitations remain in physical accessibility, tactile and audio information, and facilities for persons with disabilities and other vulnerable groups. These findings emphasize the need to strengthen interactive exhibition design by integrating it more clearly with inclusive principles in the development of museums in Indonesia. Keywords : Integrated Museum Engagement Model; Museum; Inclusive Museum; Interactive Exhibition Design; Multisensory